Circulating IL-17A Levels in Postmenopausal Women with Primary Hyperparathyroidism. (17th January 2020) - Dozio, E.; Passeri, E.; Vianello, E.; Palmieri, S.; Eller-Vainicher, C.; Corsi Romanelli, M.; Corbetta, S.
Abstract : Background . Primary hyperparathyroidism (PHPT) is a common cause of secondary osteoporosis in postmenopausal women. Th17 lymphocytes and the released cytokine IL-17A play an important role in bone metabolism. Th17 cells have been shown to be activated by PTH, and peripheral blood T cells from patients affected with PHPT express higher levels of IL-17A mRNA than controls. Aim. To investigate circulating levels of IL-17A and the ratio RANKL/OPG, as markers of osteoclastogenesis, in 50 postmenopausal PHPT women compared with postmenopausal osteoporotic non-PHPT women (n = 20 ). Results. Circulating levels of IL-17A were similarly detectable in most PHPT and non-PHPT osteoporotic women (12.9 (8.4-23.1) vs. 11.3 (8.3-14.3) pg/ml, median (range interquartile), P = 0.759 ), at variance with premenopausal women where IL-17A was undetectable. In PHPT women, any significant correlations could be detected between circulating IL-17A levels and PTH levels. Nonetheless, significant negative correlations between circulating IL-17A and ionized calcium levels (r = ‐ 0.294, P = 0.047 ) and urine calcium excretions (r = ‐ 0.300, P = 0.045 ) were found. Moreover, PHPT women were characterized by positive correlations between IL-17A levels and femur neck (r = 0.364, P = 0.021 ) and total hip (r = 0.353, P = 0.015 ) T -scores. Circulating IL-17A levels did not show any significant correlation with sRANKL, OPG, and sRANKL/OPG ratio in PHPT women. Conclusions . In postmenopausal PHPT women, circulating IL-17A levels were similar to those detected in postmenopausal non-PHPT women, showing a disruption of the relationship observed in postmenopausal osteoporosis among circulating PTH, sRANKL, OPG, IL-17A, and bone demineralization in postmenopausal PHPT women. The data support an osteogenic effect of IL-17A in postmenopausal PHPT women.